2020
DOI: 10.3390/w12092403
|View full text |Cite
|
Sign up to set email alerts
|

Underground Barrier Wall Evaluation for Controlling Saltwater Intrusion in Sloping Unconfined Coastal Aquifers

Abstract: Barrier walls are considered one of the most effective methods for facilitating the retreat of saltwater intrusion (SWI). This research plans to examine the effect of using barrier walls for controlling of SWI in sloped unconfined aquifers. The sloping unconfined aquifer is considered with three different bed slopes. The SEAWAT model is implemented to simulate the SWI. For model validation, the numerical results of the seawater wedge at steady state were compared with the analytical solution. Increasing the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
12
0
1
Order By: Relevance
“…The increase in barrier wells (BWs) was also helpful in controlling the SWI. Armanuos et al ( 2020 ) studied how the BWs control SWI in sloping unconfined aquifers and found that BWs are very effective in facilitating the retreat of SWI in coastal aquifers. Similarly, our results also indicate that SWIs are controlled by adding BWs.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in barrier wells (BWs) was also helpful in controlling the SWI. Armanuos et al ( 2020 ) studied how the BWs control SWI in sloping unconfined aquifers and found that BWs are very effective in facilitating the retreat of SWI in coastal aquifers. Similarly, our results also indicate that SWIs are controlled by adding BWs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proper management and understanding of coastal aquifers are crucial components of global water security. Comprehensive numerical models, such as SUTRA (Voss & Koch, 2001), SEAWAT (Guo & Langevin, 2002), and FEFLOW (Diersch, 2013), have been developed to simulate the SWI under various conditions (Armanuos et al, 2019(Armanuos et al, , 2020a(Armanuos et al, , 2020bGuo et al, 2020;Gao et al, 2021;Abdoulhalik et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Seawater intrusion in coastal aquifers is a worldwide problem caused, among other factors, by aquifer overexploitation related to human activities, such as irrigation and drinking water supply, and the reduction in natural groundwater recharge due to climate change [1]. To prevent or limit the deterioration of both surface water and groundwater quality due to salt-water contamination, research studies have been developed to fully comprehend the problem and identify its fundamental parameters, as well as to evaluate possible countermeasures, such as cut-off walls (e.g., [2][3][4][5][6][7][8][9][10][11][12]).…”
Section: Introductionmentioning
confidence: 99%